Application of CBCT in Oral Medicine: A Review (Academia Journal of Medicine, 2024)
Cone Beam Computed Tomography (CBCT) represents a  significant advancement in the field of Oral Medicine,  offering three-dimensional imaging that provides detailed  anatomical information. This imaging technique has  revolutionized the way clinicians diagnose, plan treatment,  and manage a wide range of dental and maxillofacial  conditions. The applications of CBCT in Oral Medicine are  vast, ranging from implantology and orthodontics to  endodontics and maxillofacial surgery. This paper explores  the key applications of CBCT in oral health care,  emphasizing its advantages over traditional two dimensional imaging techniques, and discusses the  implications of its use in clinical practice.
Keywords: Cone Beam Computed Tomography; CBCT; Dentistry; Oral Medicine